PERAN MODAL SOSIAL DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI PANTAI ZAKAT KOTA BENGKULU - Putri Gunawan, Adelia Alfina; Heriyanti, Lesti; Wijayanti, Ayu (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Along with the times, the tourism sector is one of the factors that should be taken into account, because it is a strategic asset to encourage the development of areas that have natural potential or tourist attractions. Bengkulu City has a lot of natural tourism potential which, if managed properly, can improve the regional economy. One of them is Jakat beach tourism which has been around for a long time, managed by a tourism awareness group (Pokdarwis). Pokdarwis utilizes social capital as a strategy to manage the tourist destination "jakat beach" to be more widely known by the community. The importance of community participation provides social capital in maintaining the tourist area. So social capital is a product of human relations as networks, norms, values, reciprocity and trust that have the potential for community productivity for the development of members of a community group that allows cooperation between them from a village that has tourism potential. The purpose of this research is to analyze the role of social capital in the development of the jakat beach tourist destination itself. This research uses descriptive qualitative methods, namely analyzing and presenting factual data systematically so that it can be more easily understood and concluded. In this study, the data collection techniques used were primary and secondary data collection techniques in the form of interviews, observation and documentation. Based on the results of the research, the social capital contained in the tourism awareness group (pokdarwis) has a positive influence in managing and developing jakat beach tourism.